The measurement of tibial acceleration in runners - A review of the factors that can affect tibial acceleration during running and evidence-based guidelines for its use - Sheerin, K. R.; Reid, D.; Besier, T. F. (Gait and Posture, 2019)
Background: Impact loading in runners, assessed by the measurement of tibial acceleration, has attracted substantial research attention. Due to potential injury links, particularly tibial fatigue fractures, tibial acceleration is also used as a clinical monitoring metric. There are contributing factors and potential limitations that must be considered before widespread implementation.